Physical Activity Prevalence in Caregivers of Children With Different Ages and Its Association With Their Psychological and Physical Health Problems - Byungmo Ku; Seungbeen Ghim (Asian Society of Kinesiology, 2022)
OBJECTIVES The purpose of the current study was to estimate the prevalence of meeting national physical activity guidelines among caregivers and to examine the association between meeting the guidelines and psychological and physical health problems in caregivers.. METHODS 2018 National Health Interview Survey (NHIS) datasets and the national physical activity guidelines (i.e., 150 minutes of moderate-to-vigorous physical activity per week) were used in the current study. RESULTS The prevalence of meeting national physical activity guidelines among caregivers of young children, school-aged children, and adolescents were 46.78%, 48.55%, and 46.54%, respectively. Physically active caregivers of school-aged children showed significantly lower likelihoods of anxiety and obesity compared to physically inactive caregivers of school-aged children. Physically active caregivers of adolescents showed significantly lower likelihoods of type 2 diabetes, hypertension, hyperlipidemia, obesity, neck pain, and back pain compared to physically inactive caregivers of adolescents. CONCLUSIONS As parents often experience some health problems, they should be encouraged to meet the national physical activity guidelines. Health care professionals should promote physical activity behaviors in caregivers by considering caregiver's health conditions.